“You Have Some Questions for Me?” considering Qualitative Interviewing - D. Jean Clandinin; Andrew Estefan; Vera Caine (International Journal of Qualitative Methods)
Interviewing, as a way of collecting research data, has emerged and been developed within the transition from modernist ideals to more postmodern perspectives about what constitutes knowledge. Interviewing practices range from standardized structured interviews to collect data in large-scale studies, to interviews that are more characteristic of a conversation that allow for a more expansive venture into an area of inquiry. While there are times when ideas develop over time and one can see the evolution of them, this is not as clear with the ideas of interviewing. In this state-of-the-art article, we survey the fields where interviews are visible and see the presence of different forms of interviews. Research interviews necessitate recognition of the ontological and epistemological commitments that shape research study design. A research interview cannot be crafted without attending to questions about: the purpose of the interview; the place it takes up alongside the needs, interests, and vulnerabilities of researchers and participants; the relationship between the intent for interviews and the places in which research interviews are conducted; how research interviews can open up as well as foreclose insight into experiences; and, how interviews are shaped by considerations of power and positionality. By attending to these questions, researchers can resist reducing interviews to a simplified ask-and-answer procedure.